Passport To The Millennium - Yost, Mary Grace (Teaching History: A Journal of Methods, 2001)
In the grammar school I attended in the late 1950s and early 1960s, there was no such thing as Social Studies. Instead, what we had were separate classes in History and Geography. What I recall about these two subjects is that each had big books, boring passages, and endless facts. I remember in seventh grade having to get a new bookbag halfway through the school year because my geography book had burst the buckle on my old bookbag. And I can still see myself sitting at my vanity table every June before final exams, cramming facts into my head for the test the next day, doing very well on the test, and then forgetting the information the day after that.